2020
DOI: 10.1101/2020.08.02.233536
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cross-neutralization of a SARS-CoV-2 antibody to a functionally conserved site is mediated by avidity

Abstract: Most antibodies isolated from COVID-19 patients are specific to SARS-CoV-2. COVA1-16 is a relatively rare antibody that also cross-neutralizes SARS-CoV. Here we determined a crystal structure of COVA1-16 Fab with the SARS-CoV-2 RBD, and a negative-stain EM reconstruction with the spike glycoprotein trimer, to elucidate the structural basis of its cross-reactivity. COVA1-16 binds a highly conserved epitope on the SARS-CoV-2 RBD, mainly through a long CDR H3, and competes with ACE2 binding due to steric hindranc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
113
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(123 citation statements)
references
References 74 publications
10
113
0
Order By: Relevance
“…Interestingly, the CR3022 Fab neutralized SARS-CoV-2 P384A mutant with an IC50 of 4.4 μg/ml, which is similar to that of CR3022 IgG (3.2 μg/ml) ( Figure 2). This result indicates that CR3022, unlike many other SARS-CoV-2 antibodies [21,23], does not act bivalently with the S proteins on the virus surface and, hence, neutralization is more sensitive to Fab binding affinity.…”
Section: Cr3022 Neutralizes Sars-cov-2 P384a But Not Wtmentioning
confidence: 92%
See 2 more Smart Citations
“…Interestingly, the CR3022 Fab neutralized SARS-CoV-2 P384A mutant with an IC50 of 4.4 μg/ml, which is similar to that of CR3022 IgG (3.2 μg/ml) ( Figure 2). This result indicates that CR3022, unlike many other SARS-CoV-2 antibodies [21,23], does not act bivalently with the S proteins on the virus surface and, hence, neutralization is more sensitive to Fab binding affinity.…”
Section: Cr3022 Neutralizes Sars-cov-2 P384a But Not Wtmentioning
confidence: 92%
“…Previous studies have indicated IgG bivalent binding can play an important role in mediating neutralization of SARS-CoV-2, since the neutralization potency for many antibodies is much greater when expressed as IgG rather than Fab [21,23]. Subsequently, we also tested the neutralizing activity of CR3022 Fab.…”
Section: Cr3022 Neutralizes Sars-cov-2 P384a But Not Wtmentioning
confidence: 99%
See 1 more Smart Citation
“…In both open and closed conformation, the orientation of the RBD of SARS CoV-2 when interacting with the α 7 subunit is more similar with the interaction of the closed, rather than the open, conformation of the RBD of SARS CoV. which binds to SARS-CoV-2 Spike glycoprotein to a similar region [23]. Most RNA viruses through antigenic mutation can avoid adaptive immunity of the host [35].…”
Section: Molecular Modelling Of Toxin-like Fragment Of Sars-cov and Smentioning
confidence: 99%
“…and COVA1-16 [20,21,23]. Having previously presented the 3D structural location of this "toxin-like" sequence on the Spike glycoprotein and the superposition of the modelled structure of the Neurotoxin homolog NL1 and the SARS-CoV-2 Spike glycoprotein [18], we are extending our previously published molecular modeling and docking experiments by presenting the complexes of both SARS-CoV and SARS-CoV-2 S glycoproteins with the 7 ECD of the model of human α 7 nAChR pentamer, in their "open" and "closed" conformations, ideally adopted by Spike glycoproteins.…”
mentioning
confidence: 99%